Malaysian highway landscape and maintenance. - Abd Rahman, Nordin (1990)
Malaysian highway landscape programmes at present are commonly perceived as beautification programmes of the completed highway. Thus, most of the planting programmes along highway/road are geared toward trying to beautify the ugly scars created. At the same time, highway slope maintenance is calling for more funds in order to protect the slope from failing. Our present system of management and maintenance works on slopes along highways and highway corridors needs to be reviewed and improved. As we are aware a good vegetation cover on a slope is one of the most effective ways in protecting the slope from failing in the long-term; thus landscape development along highways needs to be explored and geared toward a more ecological approach.